ANTIBACTERIAL AND ANTIFUNGAL PROPERTIES OF BACILLUS AMYLOLIQUEFACIENS - UZNU 22 BACTERIAL STRAIN - Akhmedova Mujassam Oribjon qizi (Journals Park Publishing, 2024)
This article explores the antibacterial and antifungal properties of the Bacillus amyloliquefaciens - UzNU 22 bacterial strain. The study provides a comprehensive analysis of the potential antimicrobial activity of this specific bacterial strain, shedding light on its effectiveness against both bacterial and fungal pathogens. The research methodology includes in vitro assays and possibly in vivo experiments to evaluate the efficacy of the strain's antimicrobial properties. The findings of this study could have significant implications for the development of novel antimicrobial agents and biotechnological applications. This research is valuable for scientists, microbiologists, and pharmaceutical researchers seeking to harness the antimicrobial potential of Bacillus amyloliquefaciens - UzNU 22 for various practical applications.
Keywords: Antibacterial, antifungal, Bacillus amyloliquefaciens - UzNU 22, bacterial strain, antimicrobial activity, in vitro assays, in vivo experiments, pathogens, antimicrobial agents, biotechnological applications, microbiology, pharmaceutical research.